Influence of occupational stress on interpersonal and organizational relationships: an integrative review - Jefferson Soares da Costa; Djavan Gomes Leite; Weslley Barbosa Sales; Márcio de Lima Coutinho (Open Journal of Pain Medicine - Peertechz Publications, 2023)
Objective: To investigate, through scientific literary findings, the effects of occupational stress on interpersonal relationships in the work environment. Methodology: This is an integrative literature review, with a descriptive and qualitative approach, carried out through a survey in the Scielo, Pubmed and Lilacs databases, with the words indexed in the DeCs: Psychology, Occupational Stress and Burnout Syndrome. As well as the Boolean operator ''AND'' to perform the crossing between the descriptors. Articles related to the proposed theme, published between the years 2016 to 2021, available in full, with no language restriction; in addition to theses, dissertations and monographs.  Results and discussions: The findings of the scientific literature exposed in this research could show that occupational stress has a total impact on interpersonal relationships and on emotional exhaustion, constituting a network conducive to the emergence and development of Burnout syndrome.  Final considerations: The research included in this study could unanimously prove that occupational stress leads to a decline in interpersonal and organizational relationships, which directly compromises the mental health of professionals, generating a risk of harm to the health of the worker, with the syndrome of Burnout is the most prevalent pathology in this context.